Development Of Thematic Mobile Based Islamic Education Learning In The Digital Era - Fajar Fathurahman; Marhamah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This study aims to produce models and learning media for Islamic Education Lesson Thematic Study of Falak, which was created using web-based application and can be accessed optimally via an Android-based cellular phone. This research method uses Research and Development with ADDIE development models consisting of five (5) stages. This research was conducted on Islamic educators and technical staff in the Ministry of Religion Regional Office of DKI Jakarta Province. The trial results of this study found that learning media that had been developed were feasible to be used and made it easier in the learning process and its application. The results of this study indicate that the Mobile Learning Islamic Education Lesson with the Study of Falak theme which is implemented by the Smart Learning PAI Framework model can improve trainees understanding concepts of the integration between Islamic Education, Science and Technology which are applied interactively and collaboratively